Diseño de un programa de actividades físicas para evitar el ocio deportivo en los estudiantes de la Escuela”Luz de America” del Cantòn Mejia, provincia de Pichincha, en el año lectivo 2013-2014 - Arias Chiguano, Blanca Rocío (2016)
This research was carried out at Pichincha Province, Mejía City, Aloasí Parish in the Luz America School in the school year 2013-2014, it had as objective to design a Physical Activity Program, which it helped to improve the health in a short and long term, the correct orientation of the teaching learning process, to create awareness in the teachers and students, about the importance in the sportive practice and the benefits obtained in these physical activities. The problem is presented because in this institution, there is not the importance for the physical activity and there are not basic documents for fomenting this activity in the students of the institution. For this research, it was applied the Inductive – Deductive – Synthetic - Analytical methods and as technique the survey applied to the 176 students and 18 teachers of the institution. As a result it achieved to design a physical activities program that it was applied to all students, obtaining the active participation of them.